Modernisasi Strategi Penghimpunan Dana Zakat, Infak Dan Sedekah (Studi Kasus Di Rumah Singgah Cariu) - Norma Rosyidah; Siti Nuraeni (Sekolah Tinggi Ilmu Bahasa Arab Darul Ulum Banyuanyar Pamekasan, 2023)
The presence of private zakat management (LAZ; Lembaga Amil Zakat) in charge of collecting and distributing ZIS funds is very helpful in maximizing the potential of ZIS in Indonesia to be well collected. One of the LAZ in Indonesia that operates in the collection and distribution of ZIS is Rumah Singgah. Rumah Singgah is the first LAZ to operate in Cariu, East Bogor. Rumah Singgah uses social media as a promotional medium in the collection of ZIS funds by creating creative and innovative content. TThis research aims to find out the extent to which modernization strategies play a role in the collection of ZIS in Rumah Singgah. The research method used in this study is a qualitative descriptive method, using data collection techniques by interviews, observations and documentation. The results of this study revealed that there was a significant increase in ZIS funds collected, amounting to Rp. 240,724,488 in 2021. Modernization Strategy in the collection of ZIS funds proved to increase the confidence of muzakki to entrust its ZIS funds managed by Rumah Singgah.